Longitudinal assessment of urinary ALCAM, HPX, and PRDX6 in Korean patients with systemic lupus erythematosus: implications for disease activity monitoring and treatment response - Kim, Ji-Won; Baek, Wook-Young; Jung, Ju-Yang; Kim, Hyoun-Ah; Lee, Sang-Won; Suh, Chang-Hee (Frontiers in Immunology, 2024)
Introduction: This study aimed to demonstrate the potential of activated leukocyte cell adhesion molecule (ALCAM), hemopexin (HPX), and peroxiredoxin 6 (PRDX6) as urine biomarkers for systemic lupus erythematosus (SLE).Methods: Urine samples were collected from 138 Korean patients with SLE from the Ajou Lupus Cohort and 39 healthy controls (HC). The concentrations of urine biomarkers were analyzed using enzyme-linked immunosorbent assay kits specific for ALCAM, HPX, and PRDX6, respectively. Receiver operating characteristic (ROC) curve analysis was performed to evaluate the diagnostic utility, and Pearson's correlation analysis was conducted to assess the relationships between the disease activity and urine biomarkers.Results: Patients with SLE and patients with lupus nephritis (LN) showed significantly elevated ALCAM, HPX, and PRDX6 levels compared with HCs. ALCAM, HPX, and PRDX6 showed significant diagnostic values, especially for lupus nephritis (LN), with areas under the receiver operating characteristic curve for LN was 0.850 for ALCAM (95% CI, 0.778-0.921), 0.781 for HPX (95% CI, 0.695-0.867), and 0.714 for PRDX6 (95% CI, 0.617-0.812). Correlation analysis revealed that all proteins were significantly associated with anti-double stranded DNA antibody (ALCAM, r = 0.350, p < 0.001; HPX, r = 0.346, p < 0.001; PRDX6, r = 0.191, p = 0.026) and SLEDAI (ALCAM, r = 0.526, p < 0.001; HPX, r = 0.479, p < 0.001; PRDX6, r = 0.262, p = 0.002). Results from the follow-up of the three biomarker levels in these patients revealed a significant decrease, showing a positive correlation with changes in SLEDAI-2k scores (ALCAM, r = 0.502, p < 0.001; HPX, r = 0.475, p < 0.001; PRDX6, r = 0.245, p = 0.026), indicating their potential as indicators for tracking disease activity. Discussion: Urinary ALCAM, HPX, and PRDX6 levels have diagnostic value and reflect disease activity in Korean patients with SLE, emphasizing their potential for non-invasive monitoring and treatment response evaluation.